Descriptive Epidemiological Tuberculosis in Purwakarta District, 2020-2023 - Suciati Marlianasyam; Ratna Djuwita; Brema JK Damanik (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Based on the results of the Indonesian Health Survey (SKI) in 2023, prevalence of Tuberculosis based on a history of doctor diagnosis is highest in Jawa Barat Province, at 0.47%, while the national Tuberculosis prevalence is 0.30%. Objective: This study aims to illustrate the Tuberculosis cases overview in Purwakarta District, 2020-2023. Method: This research uses a quantitative research design with a univariate descriptive analysis approach. This study utilizes secondary data from the Tuberculosis Information System (SITB). Result: Tuberculosis cases in Purwakarta District were highest in year 2022 (4703 cases). Based on gender, the highest cases occurred in males, with the peak in 2022 (2590 cases). The age group with the highest was the elderly age group, with the peak in 2022 (1253 cases). Tuberculosis Diabetes cases in 2022 reached 134 cases. The most accessed healthcare facility was hospitals (3317 cases) accessing healthcare services at hospitals. Conclusion: Tuberculosis cases in Purwakarta District peaked in 2022, with the highest distribution among males and elderly. The most common comorbidity of Tuberculosis cases is diabetes, and the highest number of visits is at hospitals, indicating potential Tuberculosis issues in Purwakarta District, thus further studies regarding the Tuberculosis status in Purwakarta District are needed.